NIH Workshop Report: sensory nutrition and disease. Issue 1 (9th December 2020) - Reed, Danielle R; Alhadeff, Amber L; Beauchamp, Gary K; Chaudhari, Nirupa; Duffy, Valerie B; Dus, Monica; Fontanini, Alfredo; Glendinning, John I; Green, Barry G; Joseph, Paule V; Kyriazis, George A; Lyte, Mark; et al.
Abstract: In November 2019, the NIH held the "Sensory Nutrition and Disease" workshop to challenge multidisciplinary researchers working at the interface of sensory science, food science, psychology, neuroscience, nutrition, and health sciences to explore how chemosensation influences dietary choice and health. This report summarizes deliberations of the workshop, as well as follow-up discussion in the wake of the current pandemic. Three topics were addressed: A ) the need to optimize human chemosensory testing and assessment, B ) the plasticity of chemosensory systems, and C ) the interplay of chemosensory signals, cognitive signals, dietary intake, and metabolism. Several ways to advance sensory nutrition research emerged from the workshop: 1 ) refining methods to measure chemosensation in large cohort studies and validating measures that reflect perception of complex chemosensations relevant to dietary choice; 2 ) characterizing interindividual differences in chemosensory function and how they affect ingestive behaviors, health, and disease risk; 3 ) defining circuit-level organization and function that link and interact with gustatory, olfactory, homeostatic, visceral, and cognitive systems; and 4 ) discovering new ligands for chemosensory receptors (e.g., those produced by the microbiome) and cataloging cell types expressing these receptors. Several of these priorities were made more urgent by the current pandemic because infection with sudden acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the ensuing coronavirus disease of 2019 has direct short- and perhaps long-term effects on flavor perception. There is increasing evidence of functional interactions between the chemosensory and nutritional sciences. Better characterization of this interface is expected to yield insights to promote health, mitigate disease risk, and guide nutrition policy.